Variables and Theories For Cryptocurrrency Adoption - Rahmatila, Aira; Subriadi, Apol Pribadi (Universitas Negeri Surabaya, 2024)
This systematic literature review paper discusses cryptocurrency. Various theories of cryptocurrency adoption have been developed to identify its factors. The expansion of adoption theory aims to address issues related from multiple perspectives. This methodology uses a Systematic Literature Review (SLR) method by filtering 270.000 reputable articles related to cryptocurrency adoption, This study aims to classify the journey of technology adoption focuses on cryptocurrency to identify the factors driving future adoption. This paper a systematic literature review study focuses on various aspects of cryptocurrency, including factors, domains, and theories of adoption and sustainability. The results of the study showed five theories underlying the implementation of cryptocurrency and found forty-three main influencing factors. Several studies also show prospects for cryptocurrency sustainability. Thus, research on the development of cryptocurrency theory and prospects is still open for further exploration research.